2020
DOI: 10.1111/bjh.16790
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic scoring systems and comorbidities in chronic myelomonocytic leukaemia: a nationwide population‐based study

Abstract: Summary Outcomes in chronic myelomonocytic leukaemia (CMML) are highly variable and may be affected by comorbidity. Therefore, prognostic models and comorbidity indices are important tools to estimate survival and to guide clinicians in individualising treatment. In this nationwide population‐based study, we assess comorbidities and for the first time validate comorbidity indices in CMML. We also compare the prognostic power of: the revised International Prognostic Scoring System (IPSS‐R), CMML‐specific progno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 53 publications
1
6
0
Order By: Relevance
“…Regarding prognosis, in the whole cohort, SIAD were not associated with a pejorative prognosis, in accordance with other studies 10,13 . We showed that among CMML patients with SIAD, autoimmune cytopenia had a significantly better OS compared with other types of SIAD.…”
Section: Figuresupporting
confidence: 91%
See 2 more Smart Citations
“…Regarding prognosis, in the whole cohort, SIAD were not associated with a pejorative prognosis, in accordance with other studies 10,13 . We showed that among CMML patients with SIAD, autoimmune cytopenia had a significantly better OS compared with other types of SIAD.…”
Section: Figuresupporting
confidence: 91%
“…CPSS and CPSS‐Mol scores, considered as the most relevant scoring systems for CMML in a contemporary practice, were not applicable in SIAD patients 13 . This result suggests that even though the mutational landscape was similar in CMML patients with or without SIAD, other factors have an impact on these scores.…”
Section: Figurementioning
confidence: 90%
See 1 more Smart Citation
“…Systemic AIDs are described in up to 25% of CMML patients, again mainly systemic vasculitis, followed by connective tissue diseases [57,68,76]. The majority of cases are CMML-1, with a progression to acute leukemia comparable with that of patients without AID [57].…”
Section: Aid In Cmml and Other Myeloid Neoplasmsmentioning
confidence: 99%
“…From 2012 and onwards, follow‐up data at 1 year and every third year after diagnosis is recorded. Compared to the Swedish Cancer Register, to which reporting is mandatory for clinicians and pathologists, the coverage was 97% for the years 2009‐2015 16 . In our data, we had access to 1‐year follow‐up for 1562 patients (53%), 3‐year follow‐up for 523 patients (18%) and 6‐year follow‐up for 26 patients (1%).…”
Section: Methodsmentioning
confidence: 99%